The PaO2/FiO2 ratio on admission is independently associated with prolonged hospitalization in COVID-19 patients - Zinellu, Angelo; De Vito, Andrea; Scano, Valentina; Paliogiannis, Panagiotis; Fiore, Vito; Madeddu, Giordano; Maida, Ivana; Zinellu, Elisabetta; Mangoni, Arduino Aleksander; Arru, Luigi Benedetto; Carru, Ciriaco; Babudieri, Sergio; et al. (The Journal of Infection in Developing Countries, 2021)
Introduction: The early identification of factors that predict the length of hospital stay (HS) in patients affected by coronavirus desease (COVID-19) might assist therapeutic decisions and patient flow management. Methodology: We collected, at the time of admission, routine clinical, laboratory, and imaging parameters of hypoxia, lung damage, inflammation, and organ dysfunction in a consecutive series of 50 COVID-19 patients admitted to the Respiratory Disease and Infectious Disease Units of the University Hospital of Sassari (North-Sardinia, Italy) and alive on discharge. Results: Prolonged HS (PHS, >21 days) patients had significantly lower PaO2/FiO2 ratio and lymphocytes, and significantly higher Chest CT severity score, C-reactive protein (CRP) and lactic dehydrogenase (LDH) when compared to non-PHS patients. In univariate logistic regression, Chest CT severity score (OR = 1.1891, p = 0.007), intensity of care (OR = 2.1350, p = 0.022), PaO2/FiO2 ratio (OR = 0.9802, p = 0.007), CRP (OR = 1.0952, p = 0.042) and platelet to lymphocyte ratio (OR = 1.0039, p = 0.036) were significantly associated with PHS. However, in multivariate logistic regression, only the PaO2/FiO2 ratio remained significantly correlated with PHS (OR = 0.9164; 95% CI 0.8479-0.9904, p = 0.0275). In ROC curve analysis, using a threshold of 248, the PaO2/FiO2 ratio predicted PHS with sensitivity and specificity of 60% and 91%, respectively (AUC = 0.780, 95% CI 0.637-0.886 p = 0.002). Conclusions: The PaO2/FiO2 ratio on admission is independently associated with PHS in COVID-19 patients. Larger prospective studies are needed to confirm this finding.